Activation of pelvic floor, lumbar and abdominal musculature during a simulated manual material handling task: a cross-sectional study - Fernanda Cabegi de Barros; Patricia Driusso; Fernanda Roberto; Mariana Vieira Batistão; Mikaela Corrêa; Tatiana de Oliveira Sato (Universidade de São Paulo, 2021)
ABSTRACT Pelvic floor muscles act synergistically with the abdominal and lumbar muscles contributing to spine and pelvic control. These muscles are activated during activities that increase intra-abdominal pressure, such as manual material handling. The aim of our study was to assess the electrical activity of the lumbar, abdominal and pelvic floor muscles during manual material handling with different loads. This is a cross-sectional study with sixteen nulliparous continent women aged between 18 and 35 years. An electromyographic system was used to evaluate the activation of the multifidus, erector spinal (iliocostal) and abdominal rectus muscles bilaterally (Trigno Wireless®, DelSys®, Boston, USA) and another for the pelvic floor muscles (Thought Technology Ltd, Canadá). Electromyographic data were collected during manual handling of three loads: light (1.5 kg), medium (4.5 kg) and heavy (11.3 kg). Repeated measures ANOVA was applied to compare the activation among loads at a 5% level of significance (α = 0.05). There was a significant increase in the activation of the lumbar and abdominal musculature as the load increases. No difference among loads was found for the pelvic floor muscle activation. Pelvic floor muscles did not increase their activation in function of the load, as occur for the lumbar and abdominal muscles in nulliparous continent women. These findings need to be confirmed for incontinent woman, since it could have clinical implications for designing both occupational tasks and pelvic floor rehabilitation.